Exploring The Role Of Vaccination In Preventing Infectious Diseases: A Public Health Perspective (Journal of Namibian Studies : History Politics Culture, 2022)
Vaccination is a cornerstone of public health, offering unparalleled protection against infectious diseases. This article explores the critical role of vaccination in preventing infectious diseases from a public health perspective. It examines historical achievements, current challenges, and future prospects of vaccination programs worldwide. Key topics include the impact of vaccines on disease burden reduction, the concept of herd immunity, challenges such as misinformation and vaccine hesitancy, and strategies for equitable access to vaccines. The article highlights the transformative power of vaccination in safeguarding public health and outlines future directions for enhancing vaccine efficacy, safety, and accessibility.